Which One is Happier? Psychological Well-Being Level of Students with Disabilities in Special or Inclusive Schools - Nisrina Nurika Agustin; Siti Ina Savira (Department of Special Education, 2021)
This research aims to prove the differences in psychological well-being (PWB) between students with disabilities in special and inclusive schools. This research is using the quantitative comparative method. The subjects are 69 students with disabilities from special schools and inclusive schools in Surabaya. This study focuses on students with disabilities such as deafness, hearing loss, physical disabilities, and other types of disabilities. The PWB level of each student is measured using Ryff’s multidimensional scales. The Mann-Whitney U analysis finds if the PWB level of students with disabilities in inclusive schools is higher than in special schools. The score of each dimension shows that purpose in life is the dimension with the highest average score in inclusive schools. Meanwhile, personal growth is the dimension with the highest average score in special schools. However, autonomy is the dimension with the lowest average score both in special schools and inclusive schools.